ANALYSIS OF THE SYMBOLIC MEANING OF PATTERMS USED IN ARCHITECTURAL MONUMENTS OF UZBEKISTAN (Conference Zone, 2022)
The following article presents the meaning and deep analysis of the patterns in the architectural buildings